2010
DOI: 10.1007/s11145-010-9287-2
|View full text |Cite
|
Sign up to set email alerts
|

Subgroups of adult basic education learners with different profiles of reading skills

Abstract: The purpose of this study was to identify subgroups of adult basic education (ABE) learners with different profiles of skills in the core reading components of decoding, word recognition, spelling, fluency, and comprehension. The analysis uses factor scores of those 5 reading components from on a prior investigation of the reliability and construct validity of measures of reading component skills (MacArthur, Konold, Glutting, & Alamprese, 2010). In that investigation, confirmatory factor analysis found that a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…This diversity in terms of multiple reading ability levels represented in the same classroom presents a challenge to researchers and practitioners trying to target component skills in order to improve reading comprehension. Recent studies have identified subgroups of adult learners with differential reading profiles based on the core component skills of decoding (Binder & Lee, 2012; MacArthur et al, 2012; Strucker et al, 2007), word recognition (MacArthur et al, 2012; Mellard et al, 2009), fluency (MacArthur et al, 2012; Mellard et al, 2009), spelling (MacArthur et al, 2012), and short-term memory (Strucker et al, 2007). For example, Binder and Lee (2012) detected four reader subgroups based on only two skills: reading comprehension and decoding.…”
Section: Discussionmentioning
confidence: 99%
“…This diversity in terms of multiple reading ability levels represented in the same classroom presents a challenge to researchers and practitioners trying to target component skills in order to improve reading comprehension. Recent studies have identified subgroups of adult learners with differential reading profiles based on the core component skills of decoding (Binder & Lee, 2012; MacArthur et al, 2012; Strucker et al, 2007), word recognition (MacArthur et al, 2012; Mellard et al, 2009), fluency (MacArthur et al, 2012; Mellard et al, 2009), spelling (MacArthur et al, 2012), and short-term memory (Strucker et al, 2007). For example, Binder and Lee (2012) detected four reader subgroups based on only two skills: reading comprehension and decoding.…”
Section: Discussionmentioning
confidence: 99%
“…We included this broad range of NRS levels in the sample based on empirical evidence that functional reading classification assessments (e.g., CASAS, TABE) do not represent adult literacy learners’ instructional needs (Greenberg, Levy, Rasher, Kim, Carter, & Berbaum, 2010; Mellard & Fall, in press; Mellard, Fall & Mark, 2008; Mellard, Woods, & Fall, in press; MacArthur, Konold, Glutting & Alamprese, submitted), and thus learners at various levels might benefit from the interventions.…”
Section: Methodsmentioning
confidence: 99%
“…Further obscuring this issue is the large amount of heterogeneity present in samples of adult learners (e.g., age, race/ethnicity, reading levels, and English language status; Lesgold & Welch-Ross, 2012). The current study attempted to curb part of this issue by including only native English speakers; however, some differences have been noted in recent work looking at component skill profiles of struggling adult readers (see Binder & Lee, 2012;MacArthur, Konold, Glutting, & Alamprese, 2012;Mellard, Fall, & Mark, 2009). Future work is needed to assess the robustness of the magnitudes of the relations among metalinguistic skills and word reading and to consider variations by demographic characteristics and reading levels.…”
Section: Limitationsmentioning
confidence: 99%